The Factors Affecting Customer Satisfaction And Behavioral Intentions In Using Moble Telecommunication Service In Vietnam - Van Hung, Tram (วารสารพุทธจิตวิทยา, 2020)
This paper focuses on identifying some the factors affecting customer satisfaction and behavioral intentions in using mobile telecommunication service in Vietnamese and It examines various stimuli, namely, value factors as expressed in terms of product offer and price and service quality dimensions. Nowadays customers have to face the situation how to choose the best mobile telecommunications service which is provided by many mobile telecommunications service companies. In addition, the mobile telecommunications service companies also face the situation that to meet the customer satisfaction in order to increase the market share. So, managers of telecom companies should be conscious of the factors affecting customer satisfaction and behavioral intentions in building these strong relationships. Before time there are a few studies relationship to the factors affecting customer satisfaction and their influence on customers’ future behavioral intention in the Vietnam mobile telecommunication industry. Therefore, nowadays this study seeks to explore which factors affect customer satisfaction in using mobile telecommunications. Furthermore, the research aims to investigate the relationship between customer satisfaction and behavioral intentions in mobile telecommunications service. This study was based on the customer’s perspectives and their experiences with mobile telecommunications service in Vietnam. Questionnaire as data collection tool was used in the conduction of this study. The findings indicated the perceived value; some elements of service quality and marketing mix play the key role in customer satisfaction. Especially, tangible, reliability and assurance of service quality are significant to customer satisfaction. Regarding to the marketing mix, only product, process, and physical evidence are significant to customer satisfaction in mobile telecommunications service in Vietnam. In addition to this, the findings also indicated that customer satisfaction plays a key role in determining customer behavioral intentions.